2018
DOI: 10.1007/s00432-018-2585-9
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 (TGFβ1) polymorphisms and haplotype structures have dual roles in breast cancer pathogenesis

Abstract: The present study indicates that TGFB1 variants have subtype-specific roles in BC and may switch from tumor suppressor to promoter during tumor development, consistent with TGFβ1 dual role in BC pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Our results are reminiscent of a recent Brazilian study, which analyzed the positive association of 4-locus (rs1800468-rs1800469-rs1800470-rs1800471) CTCG TGFB1 haplotype with BC and with Her2+ status in the dominant model, but negative association of GCCG haplotype with BC but not BC-associated features. 12 This highlights the significance of haplotype analysis in disease-association studies, as suggested elsewhere. 47 Our study had several strengths.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Our results are reminiscent of a recent Brazilian study, which analyzed the positive association of 4-locus (rs1800468-rs1800469-rs1800470-rs1800471) CTCG TGFB1 haplotype with BC and with Her2+ status in the dominant model, but negative association of GCCG haplotype with BC but not BC-associated features. 12 This highlights the significance of haplotype analysis in disease-association studies, as suggested elsewhere. 47 Our study had several strengths.…”
Section: Discussionmentioning
confidence: 53%
“…The polymorphisms included in this study were the missense rs1800472 (+791C.T, T264I), rs1800471 (+74G.C, R25Q), and rs1800470 (+29T.C, P10L), and the 5# near-gene rs1800469 (-1347C.T) variants. 12,18,19,27,34 While MAF and genotype distribution of only rs1800471 was significantly different between BC cases and controls, the genotype distribution of rs1800469 homozygous variant was significantly higher in BC cases. The rs1800469 variant lies within a binding site for YY1 (Yin Yang 1), and the transition of C with T leads to reducing the ligation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations